Efisiensi Produksi Melalui Penerapan Teknologi Reproduksi Inseminasi Buatan Pada Kawin Silang Kambing Poteh Di Desa Baipajung Kecamatan Tanah Merah Kabupaten Bangkalan - Susilowati, Suherni; Mustofa, Imam; Wahyu Suprayogi, Tri; Supriyadi; Mulyati, Sri (LOSARI DIGITAL, 2024)
Baipajung is a village with quite good potential value and needs to be developed in the agriculture, plantation and livestock sectors. Generally, in the village goats are mated naturally, namely one cage is used for 1 male goat and 3 female goats. The population of goats in Baipajung village is 488 male goats, 878 female goats and 587 goat kids, so with the livestock capital it can be used as a source of community income. The problem that occurs in Baipajung village, although the goat population is quite large, their maintenance is only traditional, just a side business as rojokoyo or as savings if they don't have money. Goat farmers want their goats after giving birth to have superior characteristics such as increased percentage of offspring, heavier weaning weight, higher quality goats or more efficient use of feed resources. The efficiency of livestock production can be increased through the application of Artificial Insemination reproductive technology in crossbreeding Poteh or local goats with Boar goat studs.